Particle size and injection temperature effect on the injection molding of SS316l powder - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; Ab. Rahman, Mohd Nizam; M. Amin, Sri Yulis; Ismail, Muhammad Hussain; Ibrahim, Murtadhahadi (University Publication Centre, Universiti Teknologi Mara, Malaysia, 2008)
Particle size and injection temperature influence on the injection of SS316L powder has been investigated. The feedstocks used for the investigation being 64 vol. % and 65 vol. %. Results found that the success of the molding process depends on the feedstock rheological properties. Fine powder particles at 64 vol. % demonstrated higher temperature sensitivity than the coarse powder feedstock. However, the coarse powder feedstock shows its sensitivity to the injection pressure. The investigation found that the injection temperature has its influence to the final quality of the compact. Injection temperature of 140 oC was found to be the optimum. However, the investigation does not found any significant on the injection temperature to the debinding rate.